Natural Additives Influence the Performance and Humoral Immunity of Broilers - Rahmani, H.R.; Speer, W. (International Journal of Poultry Science, 2005)
Animal nutrition as a scientific field is based on many basic sciences, such as chemistry, biochemistry, physiology and even microbiology. In this relation broiler production is one of the economic ways for protein supply. Regarding more than 32 antimicrobial compounds which is used in poultry production without any prescriptions and entering these compounds in human nutrition is considered more seriously. Recent advances in this field suggest using pre- and pro-biotics are more beneficial than antibiotics and have fewer disadvantages. This study was conducted to compare the effects of using an organic acid (citric acid) and natural additive (APC) on broiler performance and its relation with gut circumstances. 960 sexed Ross 308 chicken in a completely randomized design test in 6 groups with 4 replicates received corn-soybean meal based diet (control, group C) supplemented with 2% citric acid (group B) or 0.2% APC (group A). Body weight (BW), feed conversion ratio (FCR), duodenum and jejunum pH, ileum microflora, gut histological changes and serum gamma globulin were evaluated on days 21 and 42. Analyzed results and compared means by Duncan`s range test showed that microflora content of the intestine is dynamically changed by adding these compounds and decreasing the pH of intestine significantly (p< 0.05) affects broiler performance and other parameters by acting on microbial population of digestive system.